2013
DOI: 10.1016/j.neurobiolaging.2013.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cognitive reserve and cerebrospinal fluid biomarkers to the emergence of clinical symptoms in preclinical Alzheimer's disease

Abstract: Levels of β-amyloid and phosphorylated tau (p-tau), as measured in cerebrospinal fluid (CSF), have been associated with risk of progressing from normal cognition to onset of clinical symptoms during preclinical Alzheimer’s disease (AD). We examined whether cognitive reserve (CR) modifies this association. CSF was obtained at baseline from 239 participants (mean age 57.2 years) who had been followed for up to 17 years with clinical and cognitive assessments (mean follow-up 8 years). A composite score based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 49 publications
3
75
1
Order By: Relevance
“…Longitudinal studies have found that more years of education and higher premorbid IQ are associated with a later onset of dementia symptoms [21][22][23] and, following onset, cognitive decline is faster in those with these indices of higher cognitive reserve [22]. The latter phenomenon has been hypothesised to reflect increasing neuropathological load eventually overriding the protective effect of cognitive reserve.…”
Section: Dementiamentioning
confidence: 99%
“…Longitudinal studies have found that more years of education and higher premorbid IQ are associated with a later onset of dementia symptoms [21][22][23] and, following onset, cognitive decline is faster in those with these indices of higher cognitive reserve [22]. The latter phenomenon has been hypothesised to reflect increasing neuropathological load eventually overriding the protective effect of cognitive reserve.…”
Section: Dementiamentioning
confidence: 99%
“…On the contrary, individuals with low genetic AD risk and high CR levels better withstand AD pathology and, therefore, maintain longer normal cognitive functions. An interaction between CR, tau and phosphorylated tau (p-tau), but not β-amyloid levels, was demonstrated [37]. However, also an additive, rather than interacting, effect was reported for CR levels and AD biomarkers [39].…”
Section: The Interaction Between Reserves and Ad-related Biomarkersmentioning
confidence: 96%
“…Previous studies showed several significant interaction effects between levels of CR, CSF-biomarkers (β-amyloid and tau levels), genetic AD-like phenotype (APOE status), brain atrophy and the risk to develop the clinical symptoms of AD [27,[35][36][37][38]. In particular, Jack and co-workers [35] showed that people with a high risk of cognitive impairment due to AD pathophysiological processes, have both APOE 4 and low CR levels.…”
Section: The Interaction Between Reserves and Ad-related Biomarkersmentioning
confidence: 99%
“…APOE, b-amyloid levels, brain atrophy, etc.) and the risk to develop the clinical symptoms of AD (Jack et al 2013;Serra et al 2011Serra et al , 2015Soldan et al 2013;Bozzali et al 2014).…”
Section: Reserves and Ad-related Biomarkersmentioning
confidence: 99%
“…On the contrary, individuals with low genetic AD risk and high CR levels better withstand AD pathology and, therefore, maintain longer normal (2015) cognitive functions. Recently, an interaction between CR, tau and phosphorylated tau (p-tau), but not b-amyloid levels, was demonstrated (Soldan et al 2013). However, also an additive, rather than interacting, effect was reported for CR levels and AD biomarkers (Vemuri et al 2011).…”
Section: Reserves and Ad-related Biomarkersmentioning
confidence: 99%